EVALUATION OF USABILITY OF A NEONATAL HEALTH INFORMATION SYSTEM ACCORDING TO THE USER'S PERCEPTION - Lucio Padrini-Andrade; Rita de Cássia Xavier Balda; Kelsy Catherina Nema Areco; Paulo Bandiera-Paiva; Marynéa do Vale Nunes; Sérgio Tadeu Martins Marba; Werther Brunow de Carvalho; Ligia Maria Suppo de Souza Rugolo; João Henrique Carvalho de Almeida; Renato Soibelmann Procianoy; José Luiz Muniz Bandeira Duarte; Maria Albertina Santiago Rego; et al. (Sociedade de Pediatria de São Paulo, 2018)
ABSTRACT Objective: To measure the level of satisfaction regarding the usability of a neonatal health information system and identify if demographic factors can influence the usability of a health information system. Methods: A cross-sectional, exploratory study was carried out with a convenience sample of 50 users of the Brazilian Neonatal Research Network. The instrument chosen for the usability evaluation was the System Usability Scale between February and March 2017. The statistical analysis of the collected variables was carried out in order to describe the sample, to quantify the level of satisfaction of the users and to identify the variables associated with the level of satisfaction. Results: The female gender represented 75% of the sample. The mean age was 52.8 years; 58% had a doctoral degree, average time of graduation was 17 years, with area of practice in medicine (neonatology), with intermediate knowledge in computer science (74%) and mean system use time of 52 months. Regarding usability, 94% rated the system as "good", "excellent" or "better than imaginable". The usability of the system was not associated with age, gender, education, profession, area of practice, knowledge in computer science and time of system use. Conclusion: The level of satisfaction of the computerized health system user was considered good. No demographic factors were associated with the satisfaction of the users.